Protective Effect of TRPV1 against Renal Fibrosis via Inhibition of TGF-β/Smad Signaling in DOCA-Salt Hypertension - Wang, Youping (ScholarOne, 2011)
To investigate the effects of the transient receptor potential vanilloid type 1 (TRPV1) channel on renal extracellular matrix (ECM) protein expression including collagen deposition and the transforming growth factor β (TGF-β)/Smad signaling pathway during salt-dependent hypertension, wild-type (WT) and TRPV1-null (TRPV1(−/−)) mutant mice were uninephrectomized and given deoxycorticosterone acetate (DOCA)-salt for 4 wks. TRPV1 gene ablation exaggerated DOCA-salt-induced impairment of renal function as evidenced by increased albumin excretion (μg/24 h) compared with WT mice (83.7 ± 7.1 versus 28.3 ± 4.8, P < 0.05), but had no apparent effect on mean arterial pressure (mmHg) as determined by radiotelemetry (141 ± 4 versus 138 ± 3, P > 0.05). Morphological analysis showed that DOCA-salt-induced glomerulosclerosis, tubular injury and macrophage infiltration (cells/mm(2)) were increased in TRPV1(−/−) compared with WT mice (0.74 ± 0.08 versus 0.34 ± 0.04; 3.14 ± 0.26 versus 2.00 ± 0.31; 68 ± 5 versus 40 ± 4, P < 0.05). Immunostaining studies showed that DOCA-salt treatment decreased nephrin but increased collagen type I and IV as well as phosphorylated Smad2/3 staining in kidneys of TRPV1(−/−) compared with WT mice. Hydroxyproline assay and Western blot showed that DOCA-salt treatment increased collagen content (μg/mg dry tissue) and fibronectin protein expression (%β-actin arbitrary units) in the kidney of TRPV1(−/−) compared with WT mice (26.7 ± 2.7 versus 17.4 ± 1.8; 0.93 ± 0.07 versus 0.65 ± 0.08, P < 0.05). Acceleration of renal ECM protein deposition in DOCA-salt-treated TRPV1(−/−) mice was accompanied by increased TGF-β1, as well as phosphorylation of Smad2/3 protein expression (%β-actin arbitrary units) compared with DOCA-salt-treated WT mice (0.61 ± 0.07 versus 0.32 ± 0.05; 0.57 ± 0.07 versus 0.25 ± 0.05; 0.71 ± 0.08 versus 0.40 ± 0.06, P < 0.05). These results show that exaggerated renal functional and structural injuries are accompanied by increased production of ECM protein and activation of the TGF-β/Smad2/3 signaling pathway. These data suggest that activation of TRPV1 attenuates the progression of renal fibrosis possibly via suppression of the TGF-β and its downstream regulatory signaling pathway.